Uji Volume Air Pada Berbagai Varietas Tanaman Tomat (Lycopersicum esculentum Mill) - Juli Riskiyah; Ardian '; Adiwirman ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Tomato (Lycopersicum esculentum Mill) is one type of vegetable has long been recognized by the community. The tomato plants have many benefits in an effort to complement the needs of nutritious food, especially as a source of vitamins and minerals, can also be used for drugs. The low productivity of tomatoes one caused by a lack of knowledge of farmers in the use of high yielding varieties. One effort to increase productivity is the use of tomato varieties with good genetic properties such as harvesting, disease resistance, and growth and production tend to be better. In addition to the availability of nutrients, other factors that affect plant growth is the requirement of water for plants, because water is the most material constituent of plant tissues. This irrigation method is possible to apply mainly on land far from water sources or land that has limited water availability. The drip irrigation system can save water consumption, minimize water losses. The purpose of this study, to obtain varieties of tomato growth response and better production with the provision of drip irrigation, and to determine the exact volume of water in enhancing the growth and production of tomato plants.This research will be carried out experimentally by using Completely Randomized Design (CRD) consisting of 2 factors. The first factor consists of 3 varieties of tomatoes levels ie: V1: Ratna, V2: Mawar, V3: Karina, and the second factor consisted of 3 volumes of water treatment, namely A1: 100% (field capacity), A2: 75 % (75% of field capacity), A3: 50% (50% of field capacity). The results showed that the overall volume of water had no effect on the growth and production of tomato plants, but the effect on the appearance of flower varieties first. Tomato plants are the fastest flowering varieties Karina with 75% volume of water provision. Keywords: Drip irrigation, field capacity, tomatoes.